Perlindungan Terhadap Konsumen Liquid Electronic Cigarette Kadaluwarsa Melalui Media Sosial - Yuliarto Setiadi, Fathur; Nurul Fibrianti (Law Research Review Quarterly, 2025)
The trade of e-cigarette juice over social media involves a legal relationship that establishes obligations, rights, and responsibilities. Bea Cukai, as a government supervisory organization, is required to regulate the circulation of e-cigarette liquids. The topics addressed in this study are: (1) Legal protection for consumers against the sale of expired e-cigarette liquids via social media to safeguard customers from harm. (2) The role of government regulatory organizations in addressing the spread of expired e-cigarette liquid sales. This is a qualitative study that takes an empirical judicial method. The researcher used data from both primary and secondary sources. Primary data were gathered through observations, interviews, and documentation, while secondary data came from consumer protection laws, publications, and other literature. The researcher employed source triangulation and theory triangulation to test and validate the data. In this study, the data is analyzed utilizing the Milles and Huberman approach. The research results show that: (1) Consumers of e-cigarette liquid do not receive accurate and clear information regarding the expiration date on the liquid packaging, thus not obtaining the consumer rights stated in Article 4 letters (a) and (c) of the Consumer Protection Law (UUPK). (2) The affixing of excise tax on e-cigarette liquid packaging is intended to regulate circulation and limit consumption in accordance with Law Number 39 of 2007 concerning Amendments to Law Number 11 of 1995 concerning Excise Tax. The presence of excise tax to limit excise goods is an effort by the Government to increase state revenue and control products with negative impacts.